Sistem Informasi Geografis Sumber Daya Air Kabupaten Klaten - Puspitasari, Norma; Wahyudi, Muhammad Hari; Agustina, Sinta (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2021)
Water is one of the sources of human life that flows to a lower place without knowing administrative boundaries. Its existence follows the hydrological cycle which is closely related to weather conditions in an area so that its availability is uneven at all times and regions. Water resources consist of water, water resources and water resources contained therein. In order to support Government Regulation Number 42 of 2008 concerning sustainable management of water resources, one of the responsibilities of the government and local governments is to manage water resources information systems. In the current system, the management of water resources in Klaten Regency is still manual and not computerized properly, so data collection on water resources is less accurate and precise. The purpose of this system is to make it easier to collect data on water resources in Klaten Regency. This system is made using the Waterfall method starting from a system that is carried out sequentially with needs analysis, system design, program coding, program testing, and program implementation. The result of the system is a website that is made with a good design so that it is easy to use in inputting data.